1996
DOI: 10.1089/hum.1996.7.16-1971
|View full text |Cite
|
Sign up to set email alerts
|

High-Yield Production of pBR322-Derived Plasmids Intended for Human Gene Therapy by Employing a Temperature-Controllable Point Mutation

Abstract: Production of large quantities of highly purified plasmid DNA is essential for gene therapy. A low-copy-number pBR322-derived plasmid (VCL1005) was converted to a high-copy-number plasmid (VCL1005G/A) by incorporating a G-->A mutation that affects initiation of DNA replication from the ColE1 origin of replication. Because the phenotypic effect of this mutation is enhanced at an elevated temperature, a further increase in yield was achieved by changing the growth temperature from 37 degrees C to 42 degrees C at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(47 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…With this culture procedure larger amounts of plasmid pIDKE2 can be obtained in DH10B cells. Several researchers have reported the behaviour of plasmid volumetric yield (mg/L) for different fermentation strategy (Figure 1) (Diogo, 2000(Diogo, , 2001Durland, 1999;Lahijani, 1996;Shmidt, 2001Shmidt, , 2003Wang, 2001). As it is shown, plasmid production under non optimized laboratory conditions invariably leads to very low volumetric titters (5-70 mg/L) and DNA production processes that employ simple batch cultivation technology yield relatively low biomass and correlatively support low plasmid volumetric yields too (<100 mg/L).…”
Section: High Cell Density Culturementioning
confidence: 99%
“…With this culture procedure larger amounts of plasmid pIDKE2 can be obtained in DH10B cells. Several researchers have reported the behaviour of plasmid volumetric yield (mg/L) for different fermentation strategy (Figure 1) (Diogo, 2000(Diogo, , 2001Durland, 1999;Lahijani, 1996;Shmidt, 2001Shmidt, , 2003Wang, 2001). As it is shown, plasmid production under non optimized laboratory conditions invariably leads to very low volumetric titters (5-70 mg/L) and DNA production processes that employ simple batch cultivation technology yield relatively low biomass and correlatively support low plasmid volumetric yields too (<100 mg/L).…”
Section: High Cell Density Culturementioning
confidence: 99%
“…agitation, and an air flow rate of 5 L/h. For increased copy number, the temperature was raised to 42ºC at mid-log phase (Lahijani et al 1996). After bacterial alkaline lysis, the mixture was neutralized and clarified by tangential flow filtration (TFF) using a nominal molecular weight cutoff TFF polyethersulfone membrane (1,000,000 Da).…”
Section: Bacterial Culture and Purification Of Pvegf 121mentioning
confidence: 99%
“…In the past twenty years, many efficient strategies for recombinant-cell fermentation had been developed to attain high productivity of proteins in E. coli, B. subtillis, yeast, even in animal cell culture systems (SivaKesava et al, 1999;Ebisu et al, 1992;Cheng et al, 1997;Churgay et al, 1997). However, few papers were focused on the plasmid DNA production in recombinant E. coli fermentation process (Lahijani et al, 1996;O'Kennedy et al, 2000). It was reported that the media composition affected cell growth rate, and thus influenced plasmid copy number (Kleinman et al, 1986;Kim and Shuler, 1990).…”
Section: Introductionmentioning
confidence: 99%